Application of dual-fuel combustion over the full operating map in a heavy-duty multi-cylinder engine with reduced compression ratio and diesel oxidation catalyst. (15th June 2018) - Ren, Shuojin; Wang, Boyuan; Zhang, Jun; Wang, Zhi; Wang, Jianxin
Highlights: Dual-fuel combustion fueled with gasoline and diesel was applied over the full operating map. The mode-switching strategy was optimized using a dedicated experimental procedure. Euro V emission regulation was fulfilled in the cycle test with a simple after-treatment device. With a lower compression ratio, better combustion and emission performance was achieved. Diesel oxidation catalyst effects were studied using the particle number-size distribution analysis. Abstract: This research focuses on the potential of the dual-fuel combustion engine fueled with regular gasoline and diesel to meet the Euro V emission standard over the whole operating range with a simple after-treatment system. For this purpose, a mode-switching strategy was investigated in this work. The engine maps of this strategy were obtained using a dedicated experimental procedure on a modified heavy-duty multi-cylinder engine. The switching of dual-fuel modes mainly depended on the engine load. At 25% engine load, fully premixed reactivity controlled compression ignition combustion was applied to achieve high efficiency and low emission combustion. At operating conditions higher than 50% load, homogeneous charge induced ignition combustion with up to three diesel injections (pre-, main and post-injections) was applied. Then, the effects of compression ratio on the dual-fuel combustion over the full operating map were explored and analyzed in detail. It was found that in spite of a slight increase in the fuel consumption, better combustion and emission performance over the whole operating map could be achieved in the dual-fuel combustion with a lower compression ratio. Finally, the effects of diesel oxidation catalyst were also investigated. The exhaust temperatures of this dual-fuel strategy were higher than the diesel oxidation catalyst light-off temperature, ensuring an effective conversion of the total hydrocarbon and carbon monoxide emissions. Furthermore, from the particle number-size distribution analysis, it was found that reactivity controlled compression ignition was dominated by the nucleation mode particles, while homogeneous charge induced ignition was dominated by the accumulation mode particles which tended to increase as the load increased. In addition, with a lower compression ratio of 16:1 and the application of diesel oxidation catalyst, the cycle-averaged regular emissions of the mode-switching combustion strategy could meet the Euro V emission standard simultaneously in the European Stationary Cycle test.